Positive correlation of Hypertension and Cognitive Function of Elderly - Nanik Dwi Astutik; Felisitas A Sri S; Ifa Pannya Sakti (STIKes Patria Husada Blitar, 2022)
Biological changes in the elderly are one of the triggers for the emergence of hypertension which can cause changes in cognitive function. The purpose was to analyze the correlation between hypertension and cognitive function in the elderly. The design was correlation descriptive research design with the cross-sectional approach. The sampling technique was purposive sampling, the number of samples of respondents was 56 people. The research was conducted at Integrated Healthcare Center Elderly, Malang City. The instrument used to while the cognitive function in the elderly uses the MMSE. Analysis used the Spearman rank test with an alpha value of 0.05 (95% CI). The results showed that there was a significant correlation between hypertension and cognitive function in the elderly (r=0.532 and p=0.000). The direction of the correlation is positive, meaning that the more severe hypertension suffered by the elderly, the more severe they will tend to experience more severe cognitive function impairments. Based on the results of this study, it is recommended for people with hypertension do blood pressure screening and undergo hypertension treatment regularly. This is very important so that prevention and treatment can be carried out earlier to prevent more severe cognitive impairment.